Taxonomy and DNA Sequencing of Crematogaster coriaria Mayr, 1872 (Hymenoptera: Formicidae), with Redescriptions of the Worker, Queen, and Male Castes. (13th October 2015) - Hosoishi, Shingo; Ogata, Kazuo
Abstract : Crematogaster coriaria Mayr, 1872, is revised based on the nest series samples. The following new synonymies are proposed: C. coriaria Mayr, 1872 =   C. coriaria fraudatrix Forel, 1911 syn. nov.   =   C. spengeli Forel, 1912 syn. nov.   =   C. spengeli taipingensis Forel, 1913 syn. nov. Worker, queen, and male castes of C. coriaria Mayr, 1872, are redescribed. The polymorphism of C. coriaria Mayr, 1872, was also discussed. DNA sequences were generated for C. coriaria Mayr, 1872, using an amplification of second half region of the mitochondrial gene COI with a total of 711 bp. The interspecific COI divergence is 17.4% for C. coriaria Mayr, 1872, and C. modiglianii Emery, 1900.